Impact of Initial Cyclic Loading on Mechanical Properties and Performance of Nafion - David Vokoun; Sneha Samal; Ivo Stachiv (Sensors, 2023)
Nafion possesses many interesting properties such as a high ion-conductivity, hydrophilicity, and thermal and chemical stability that make this material highly suitable for many applications including fuel cells and various (bio-)chemical and physical sensors. However, the mechanical properties of a Nafion membrane that are known to be affected by the viscoplastic characteristics of the material itself have a strong impact on the performance of Nafion-based sensors. In this study, the mechanical properties of Nafion under the cyclic loading have been investigated in detail. After cyclic tensile loading (i.e., maximum elongation about 25% at a room temperature and relative humidity about 40%) a time-dependent recovery comes into play. This recovery process is also shown being strain-rate dependent. Our results reveal that the recovery behavior weakens after performing several stress–strain cycles. Present findings can be of a great importance in future design of various chemical and biological microsensors and nanosensors such as hydrogen or glucose ones.